Paisagem, interidentidade e colonialismo em As Areias do Imperador 1: Mulheres de Cinzas, de Mia Couto - Vassoler, Sheila (2019)
Published in 2015, the novel Women of Ashes, the first volume of Mia Couto's The Sands of the Emperor trilogy, portrays the time when southern Mozambique was ruled by Ngungunyane, the last of the emperors of the southern half of the country. The relationship between the landscape and the inter-American regimes in the representation of Portuguese colonialism in the nineteenth century is evidenced in this work with the objective of investigating the integration of the subject with his environment and with the Other in the time in which they live, besides showing the consequences of this conviviality in the identity representations of both the colonizer and the colonized. In this sense, the analysis is based on the theoretical assumptions of Michel Collot, with Merleau-Ponty's landscape studies and reflections on the phenomenology of perception, as well as the works of other scholars: Stuart Hall, Homi Bhabha, and Zygmunt Bauman, who contemplate cultural and identity relations; Boaventura de Sousa Santos, Albert Memmi and Eduardo Lourenço who address the reflections on the interidentity issues, which are related to the relations between colonizer and colonized.